Ocular teratoid medulloepithelioma in a northern red-shouldered macaw: case report and literature review. (May 2021) - Leal de Araújo, Jeann; Arruda, Alice C. A. M.; Santos, Nayadjala T. A.; Dias, Glenison F.; Nery, Thiago F. L.; Del Piero, Fabio; Ploeg, Richard; Porter, Brian F.; Langohr, Ingeborg M.
A 4-mo-old northern red-shouldered macaw ( Diopsittaca nobilis ) was admitted to the veterinary hospital of the Arruda Câmara Zoo, in the State of Paraiba, Brazil, for investigation of an orbital mass. Given rapid progression and lack of response to treatment, the bird was euthanized, and an autopsy was performed. Histologically, the mass consisted of a retrobulbar invasive tumor characterized by tubular and rosette-like structures, with interspersed heteroplastic tissues, such as aggregates of neuroglial cells and islands of hyaline cartilage. The tumor was immunopositive for pancytokeratin, GFAP, NSE, and S100. These findings were compatible with an ocular teratoid medulloepithelioma, a neoplasm best described in humans but also reported rarely in young cockatiels and African Grey parrots.